NIVEL DE SATISFACCIÓN DE USUARIOS ATENDIDOS EN EL CONSULTORIO DE ODONTOLOGÍA DE UN HOSPITAL DE CAJAMARCA, PERÚ 2024. UN ESTUDIO TRANSVERSAL - Tapia Mantilla, Angel Jhosep (2025)
Objective: The objective of the study was to establish the level of satisfaction of each of the patients seen in the dentistry office of the Cajamarca Regional Teaching Hospital during the year 2024. Materials and methods: For this purpose, a quantitative, descriptive and cross-sectional methodology was used, and a simple randomized probabilistic design was used to select the sample, with 340 participants. As for data acquisition, the SERVQUAL measurement instrument modified for the dental office was used. Results: Regarding the satisfaction of users treated in the dental service, 39.4% were dissatisfied, 34.4% were satisfied, and 26.2% were satisfied. Conclusion: The results revealed a significant level of dissatisfaction, reflected at 39.4%, underscoring the need to continuously optimize service quality to maintain high levels of satisfaction.